2004
DOI: 10.1038/ncb1182
|View full text |Cite
|
Sign up to set email alerts
|

Actin is part of pre-initiation complexes and is necessary for transcription by RNA polymerase II

Abstract: Actin is abundant in the nucleus and has been implicated in transcription; however, the nature of this involvement has not been established. Here we demonstrate that beta-actin is critically involved in transcription because antibodies directed against beta-actin, but not muscle actin, inhibited transcription in vivo and in vitro. Chromatin immunoprecipitation assays demonstrated the recruitment of actin to the promoter region of the interferon-gamma-inducible MHC2TA gene as well as the interferon-alpha-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
292
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(316 citation statements)
references
References 38 publications
16
292
0
1
Order By: Relevance
“…That indicated that expression of certain target genes were regulated because b-actin is a co-factor of RNA polymerase II in gene transcription [25,26]. Actin is abundant in the nucleus and has been implicated in transcription [25] and RNA polymerase II is present in the nucleolus-like body at all transcriptional states of the oocyte nucleus [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That indicated that expression of certain target genes were regulated because b-actin is a co-factor of RNA polymerase II in gene transcription [25,26]. Actin is abundant in the nucleus and has been implicated in transcription [25] and RNA polymerase II is present in the nucleolus-like body at all transcriptional states of the oocyte nucleus [27].…”
Section: Discussionmentioning
confidence: 99%
“…Actin is abundant in the nucleus and has been implicated in transcription [25] and RNA polymerase II is present in the nucleolus-like body at all transcriptional states of the oocyte nucleus [27]. Actin and RNA polymerase II co-localize in nucleus [25,28]. Possibly when the expression of some genes, such as ICAM-1 and integrin b1 is changed, the b-actin and RNA polymerase II are recruited and transferred to nucleolus.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have provided evidence that nuclear actin associates with three types of nuclear complexes involved in gene expression: chromatin remodeling complexes, [10][11][12] ribonucleoprotein particles 13,14 and the three RNA polymerases. [15][16][17] CapG as a nuclear actin-binding protein could play a role in preventing the nuclear actin from polymerizing and keeping it in a monomeric globular or a short oligomeric form. Thus, it could have some indirect influence on the regulation of gene expression.…”
mentioning
confidence: 99%
“…Interestingly, the formation of actin rods implies not only an alteration of the synapses but it also contributes to an impairment of gene transcription. It has been reported that both nuclear actin and cofilin are part of the preinitiation complex and are implicated in the transcription of most RNA polymerase II genes, [85][86][87] directly connecting actin filaments to transcriptional regulation. When the actin-cofilin equilibrium is perturbed by oxidative stress and excitotoxicity, transcription is affected leading to gene repression.…”
Section: Multiple Targets For Gene Repression In the Nucleus Transglumentioning
confidence: 99%